Development of Student report card system (SRCS) / Wan Fatin Amirah Wan Mamat - Wan Mamat, Wan Fatin Amirah (2014)
The thesis research is about development of Student Report Card System (SRCS) for Sekolah Kebangsaan Seberang Tayor (SKST) Kemaman, Terengganu. This system is to assist the school administrator and class teachers to manage the student report card. The teacher will be able to keep a record of student information and student result twice per year. Student parents also use this system to view and validate their child’s report card. This research is as a solution to the problem occurs in handling student report card and other problem faced by SKST. Some problems that have been identified such as SKST currently using manual system that require much time in handling report card and some parents did not receive the report card and validate it. The purposes of this system are to provide the information about student performance to the parents and also to help the parents who are busy working who cannot come to the school to check their child’s report card. This research has three objectives that need to be achieved. The first objective is to identify requirements of SRCS for SKST. The second objective is to design SRCS for SKST and the third objective is to develop and demonstrate SRCS for SKST. Several methods have been applied for this research which is interview session with teachers at SKST to gather requirement about student report card handling and review related journals and articles for literature review to understand the process applied in this project. The researcher has chosen Rapid Application Development (RAD) in developing this system. From using SRCS, many advantages can be received from it. The system can help the SKST to improve their school performance and help teachers to manage the student report card. In the future work, this system will be able in mobile application.